Graphs in biomedical image analysis and integrating medical imaging and non-imaging modalities : second International Workshop, GRAIL 2018 and first International Workshop, Beyond MIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings /: second International Workshop, GRAIL 2018 and first International Workshop, Beyond MIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings. (2018) - Unknown
No abstract available